2022
DOI: 10.3389/fnbot.2022.1066714
|View full text |Cite
|
Sign up to set email alerts
|

Design and dynamic analysis of jumping wheel-legged robot in complex terrain environment

Abstract: Wheel-legged robots have fast and stable motion characteristics on flat roads, but there are the problems of poor balance ability and low movement level in special terrains such as rough roads. In this paper, a new type of wheel-legged robot with parallel four-bar mechanism is proposed, and the linear quadratic regulator (LQR) controller and fuzzy proportion differentiation (PD) jumping controller are designed and developed to achieve stable motion so that the robot has the ability to jump over obstacles and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Moreover, they are deployed by military forces to conduct reconnaissance in rugged landscapes such as reported in [33]. On the other hand, in manufacturing industries, wheel-legged robot agility has been leveraged to efficiently manage the materials within intricate industrial settings such as reported in [34]. At the forefront of this groundbreaking field stands Swiss-Mile, a creation of ETH Zurich's Robotic Systems Lab.…”
Section: Evolution and Terrain Adaptability In Bipedal Wheel-legged R...mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, they are deployed by military forces to conduct reconnaissance in rugged landscapes such as reported in [33]. On the other hand, in manufacturing industries, wheel-legged robot agility has been leveraged to efficiently manage the materials within intricate industrial settings such as reported in [34]. At the forefront of this groundbreaking field stands Swiss-Mile, a creation of ETH Zurich's Robotic Systems Lab.…”
Section: Evolution and Terrain Adaptability In Bipedal Wheel-legged R...mentioning
confidence: 99%
“…BWL robots, which combine the agility of legged robots with the mobility of wheeled counterparts, are reshaping the landscape of mobile assistive systems. These robots feature three primary locomotion modes: bipedal walking, bipedal skiing, and rolling, enabling both stable walking and rapid rolling [4]- [7]. Their ability to seamlessly switch between these modes is crucial for adapting to diverse environments [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [42], a cascade PID controller was proposed for a bipedal leg-wheeled robot to guarantee the stabilization and driving. In [49], LQR controller and fuzzy PD controller were investigated on a new type of wheel legged robot with parallel four-bar mechanism for stable movement and jumping over obstacles.…”
Section: Introductionmentioning
confidence: 99%